2020
DOI: 10.31234/osf.io/jrpfd
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Political Ideology and the Outbreak of COVID-19 in the United States

Abstract: At the state level within the United States, did political ideology predict the outbreak of the novel coronavirus (COVID-19)? Throughout March 2020, the United States became the epicenter of the COVID-19 pandemic, recording the most cases of any country worldwide. The current research found that, at the state level within the United States, more conservative political ideology predicted delayed implementation of stay-at-home orders and more rapid spread of COVID-19. Effects were significant across two distinct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 2 publications
1
18
0
Order By: Relevance
“…Aligned with prior research, we found that, although intentions to socially distance were relatively high among both liberals and conservatives, conservatives tended to have lower intentions to socially distance than liberals. This research is thus part of a growing body of evidence identifying a consistent ideological gap in social distancing (Gollwitzer et al, 2020;Plohl & Musil, 2020;Rosenfeld, 2020;Rothgerber et al, 2020); evidence that is critical to understanding factors that might contribute to further spread of the virus. For example, reduced compliance with social distancing recommendations in strongly pro-Trump counties was associated with a 27% higher growth rate in COVID-19 infections in those counties, revealing the importance of increasing conservatives' social distancing behavior (Gollwitzer et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Aligned with prior research, we found that, although intentions to socially distance were relatively high among both liberals and conservatives, conservatives tended to have lower intentions to socially distance than liberals. This research is thus part of a growing body of evidence identifying a consistent ideological gap in social distancing (Gollwitzer et al, 2020;Plohl & Musil, 2020;Rosenfeld, 2020;Rothgerber et al, 2020); evidence that is critical to understanding factors that might contribute to further spread of the virus. For example, reduced compliance with social distancing recommendations in strongly pro-Trump counties was associated with a 27% higher growth rate in COVID-19 infections in those counties, revealing the importance of increasing conservatives' social distancing behavior (Gollwitzer et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Poll Shows Partisan Differences Over How Seriously People Are Taking Coronavirus ~NPR Despite the fact that COVID-19 similarly affects people regardless of where they lie on the political spectrum, the evidence suggests that conservatives and liberals are responding differently to the coronavirus crisis. Indeed, recent media accounts imply that conservatives are less worried than liberals about the virus (NPR 2020; The Atlantic 2020), and an emerging body of research shows that conservatives are less likely to adopt recommended behavioral changes to mitigate the spread of COVID-19 (Allcott et al 2020;Rosenfeld 2020). Given that up to 80% of infections are mild or asymptomatic (WHO 2020a), conservatives' reluctance to engage in preventive behavior is worrisome because behaviors that mitigate the spread of coronavirus, such as social distancing, are crucial to reducing the number of COVID-19 infections (Goldberg et al 2020) and protecting others at greater risk (CDC 2020).…”
Section: Red and Blue America Aren't Experiencing The Same Pandemic ~mentioning
confidence: 99%
“…Instead, these findings might suggest that conservatives should be more willing to engage in coronavirus-prevention behaviors because they are more sensitive to threats. However, in the context of the coronavirus crisis, most research has suggested otherwise: that conservatives are less likely to take actions that might limit the threat of COVID-19 (Allcott et al 2020;Rosenfeld 2020).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, van Holm et al (2020) reported that liberals and moderates made fewer trips outside their homes than conservatives and that liberals and moderates were more likely to conform to the specific behaviors suggested by the government as a means of slowing the spread of the virus. Additionally, Rosenfeld (2020) found that states with more conservative ideologies delayed stay-at-home orders and facilitated a more rapid spread of the coronavirus, while Wong (2020) stated that some U. S. citizens believe that requiring masks is a civil liberties infringement. Consequently, it was important to verify that the sample did not skew toward one dominant ideology.…”
Section: Data Collection and Measuresmentioning
confidence: 99%